Navigating New Horizons: Inaugural Words from the Editor-in-Chief (International Journal of Multidisciplinary Perspectives in Higher Education, 2023)
It is with great enthusiasm and honor that I assume the role of Editor for our esteemed journal – The International Journal of Multidisciplinary Perspectives in Higher Education. As I embark on this journey, I am filled with a profound sense of responsibility and commitment to maintaining the high standards of academic excellence that this publication has long been known for.